KAJIAN KANTONG SEMAR DI HUTAN LINDUNG GUNUNG MAHAWU - Anggel Ulundeda; Marthen T. Lasut; Euis F.S. Pangemanan (Universitas Sam Ratulangi, 2022)
ABSTRAK This study aims to determine the presence of pitcher plants in HL Gunung Mahawu. The research was carried out from August to October 2021. In collecting semar bag data, observations were divided into 8 points, namely: 1. Determination of Coordinate Points 2. Observation of the type of pitcher plants, 3. Number of individuals, 4. Number of bags, 5. Morphology of pitcher plants, 6. Elevation, and 7. Slope. This observation was carried out from morning to evening at 07:00-17:00 WITA. HL Gunung Mahawu found 6 locations for the distribution of pitcher plants which grow on the edge of the crater of Gunung Mahawu, pitcher plants in HL Gunung Mahawu found 1 species, namely N. maxima, totaling 936 individuals. This type of pitcher plants has two different color variations in the bag, namely green and green with brownish patterns, the total number of bags is 1,076, on average in one individual there are 6 to 8 bags. N. maxima found in HL Gunung Mahawu grows in open areas at an elevation of 1295-1323 m with a slope of 46% - 54%. Keywords: Study of pitcher plant, HL Gunung Mahawu